SFL analysis: An investigation of students’ use of cohesive devices in exposition text - Rojab Siti Rodliyah; Alfath Eka Liani (Universitas Pendidikan Indonesia, 2022)
The 2013 Indonesian Curriculum stipulates that one of the students’ basic competencies in the English subject is to produce an analytical exposition text. The students are required to write the text persuasively and cohesively. These requirements make them consider composing such a text as a challenging task. This study investigated students’ utilization of cohesive devices in writing analytical exposition texts and examined their inaccurate uses. It attempted to demonstrate the underlying issues that caused the inaccurate uses of cohesive devices and to seek the solutions. The study employed Qualitative Content Analysis (QCA) of six analytical exposition texts written by 11th grade students in Cimahi. They were collected using purposive sampling and were analyzed using Halliday and Hasan’s cohesion framework. This study revealed that lexical cohesion served as the most frequently used cohesive devices in the students’ texts followed by reference and conjunction. Inaccurate uses of cohesive devices were also found. Most of the reference and conjunction devices were misused, whilst repetition devices were redundantly utilized. These findings showed that although the students were skilful in presenting relevant supporting arguments and making their text personal, they still experienced confusion when utilizing cohesive devices. Therefore, teachers need to equip the students with adequate knowledge concerning text cohesiveness as well as to provide more practice and feedback to improve their skills in writing an analytical exposition text.